Implementing a Simple Water Filtration System to Enhance Water Quality in Rural Communities: A Case Study of Kalong Liud Village - Hasanah, Uswatun; Sutanto; Iryani, Ani; Zulfa, Naura Devana; Pratiwi, Fany Dwi; Darussalam, Muhamad Virgi (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2025)
In response to global challenges outlined by the United Nations Sustainable Development Goals (SDGs), this study addresses the urgent need for clean water in Klong Liud Village, Bogor Regency. The village struggles with inadequate water sources due to shallow wells contaminated by sedimentary rocks, forcing reliance on the Cikaniki River, which fails to meet Indonesian water quality standards. This research implements a Simple Water Filtration System to improve local water quality, employing a multi-stage filtration process that includes activated carbon, aquarium filters, and ijuk (palm fiber). The filtration unit was designed with three sequential stages and constructed together with local residents to ensure community participation and practical skill transfer. Post-implementation observations showed clear improvements in water appearance, odor, and acceptability for domestic use, indicating that the system effectively enhanced physical water quality. Methodologically, the project involved a field survey to assess water quality issues, community engagement to ensure local participation, and the construction of a filtration system capable of providing clean water. The evaluation post-implementation confirmed significant improvements, transforming initially polluted water into clean, odorless water suitable for daily use. This study highlights the effectiveness of simple filtration technologies in addressing water quality issues in rural settings and underscores the importance of sustainable solutions in achieving global water accessibility targets.